2020
DOI: 10.1002/jso.25927
|View full text |Cite
|
Sign up to set email alerts
|

Orbital metastases from breast cancer: A single institution case series

Abstract: Background and Objectives Among orbital tumors, metastatic lesions have a prevalence of 1% to 13%; on the other hand, breast cancer is the most common malignancy causing orbital metastases. The aim of this study is to present our experience dealing with orbital metastases caused by breast cancer, to assess characteristics and clinic‐pathological data of patients suffering from this rare occurrence and to find indexes related with their prognosis and survival. Methods Records of 28 patients diagnosed with orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…A study conducted by Parrozzani et al reported that patients with choroidal metastases are more likely to have an ER-positive and PR-positive primary breast cancer than patients with breast cancer metastasizing to any other location [26]. In a recent cohort description of orbital metastases by Sindoni et al, they were all ER positive [27]. In our study, ER, PR, and HER2/neu receptor status of primary tumors that led to OM did not differ significantly from the receptor status of other primary breast tumors in a large institutional database of patients with metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Parrozzani et al reported that patients with choroidal metastases are more likely to have an ER-positive and PR-positive primary breast cancer than patients with breast cancer metastasizing to any other location [26]. In a recent cohort description of orbital metastases by Sindoni et al, they were all ER positive [27]. In our study, ER, PR, and HER2/neu receptor status of primary tumors that led to OM did not differ significantly from the receptor status of other primary breast tumors in a large institutional database of patients with metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case in patients with no evident orbital or ocular masses. We noted that some primary cancers tend to infiltrate specific orbital tissues, such as breast cancers localizing within the orbital fat pad due to the local hormonal patterns, and melanomas invading and enlarging the extraocular muscles as seen clearly on MRI scans [ 39 , 40 ]. Similarly, prostate and liver cancers commonly infiltrate the orbital bony structures inducing osteoblastic or osteoclastic reactions, and this is better identified on CT scans [ 7 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported an incidence of orbital metastasis from breast cancer of 0.13%. [ 8 ] The average time from the diagnosis of breast cancer to the development of orbital metastases was reported to be approximately 5 years. [ 8 9 ] Orbital metastatic disease is one of the known indications for orbital biopsy, especially in the absence of previous history of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] The average time from the diagnosis of breast cancer to the development of orbital metastases was reported to be approximately 5 years. [ 8 9 ] Orbital metastatic disease is one of the known indications for orbital biopsy, especially in the absence of previous history of cancer. [ 10 ] Our patient had a denial of her breast cancer and was accordingly not compliant to any therapy over 10 years.…”
Section: Discussionmentioning
confidence: 99%